2021
DOI: 10.1021/acs.analchem.0c05165
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy-Based 3D Analysis of Odontogenic Differentiation of Human Dental Pulp Stem Cell Spheroids

Abstract: Numerous efforts have been made to establish three-dimensional (3D) cell cultures that mimic the structure, cell composition, and functions of actual tissues and organs in vitro; however, owing to its intrinsic complexity, precise characterization of 3D differentiation remains challenging and often results in high variations in the resulting differentiated spheroids. This study reports a 3D Raman mapping-based analytical method that helps us to identify the crucial factors responsible for inducing variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Bacteria play an important role in the process of biocalcification, biosilication and biomineralization. In organisms, bacteria-mediated calcification can be found in crustaceans, marine organisms, plants and human organs. Calcification in tumor tissue is supposed to be related to bacteria. , The appearance of dental plaque is the cause of bacteria, and the appearance of magnetosomes in bacteria is also the cause of biosynthesis. , A large number of bacteria can produce acidic polysaccharide matrix on the surface of bacteria, provide nucleation sites for mineral deposition, and contribute to biomineralization. This provides a synthetic basis for the intrabacterial biosynthesis of nanoparticles with physicochemical properties.…”
Section: Biosynthesis Systemsmentioning
confidence: 99%
“…Bacteria play an important role in the process of biocalcification, biosilication and biomineralization. In organisms, bacteria-mediated calcification can be found in crustaceans, marine organisms, plants and human organs. Calcification in tumor tissue is supposed to be related to bacteria. , The appearance of dental plaque is the cause of bacteria, and the appearance of magnetosomes in bacteria is also the cause of biosynthesis. , A large number of bacteria can produce acidic polysaccharide matrix on the surface of bacteria, provide nucleation sites for mineral deposition, and contribute to biomineralization. This provides a synthetic basis for the intrabacterial biosynthesis of nanoparticles with physicochemical properties.…”
Section: Biosynthesis Systemsmentioning
confidence: 99%
“…In 2021, RAMAN spectroscopy was used to find the factors responsible for stem cell differentiation in spheroids formed by aggregation of human DPSCs. This research showed that the differentiation and acquisition of the 3D structure is mainly related to the diffusion of nutrients, morphogens, and growth factors within the culture medium [ 119 ].…”
Section: Overview Of Different Types Of Dental Stem Cellsmentioning
confidence: 99%
“…Some of these methods are still in the research stage and are not ready to be adopted for large-scale manufacturing. The manufacturing methods of DPSC spheroids have also emerged in an endless series, including but not limited to serum-free medium culture[ 144 , 145 ], culturing on Matrigel[ 146 ], special 3D Petri dish culture[ 135 , 147 ], low or ultralow attachment culture plates[ 62 , 148 ], culturing on gelatin methacrylamine/poly(ethylene glycol) diacrylate (GelMA/PEGDA) composite hydrogels[ 149 ], coculturing with microparticles with a leaf-stacked structure based on polycaprolactone[ 150 ], HD or molded parafilm-based methods[ 151 ]. Most of these methods belong to the classification of the aforementioned technologies.…”
Section: Derivatives Of Dpscsmentioning
confidence: 99%